The Role of Principal's Leadership Style and Motivation in Improving Superior Teacher Performance at SMA Negeri 7 Cirebon City - Fanendra Priutama Affandi; Safrudin Safrudin; Noveria Susijawati; Sunimah Sunimah (Eduvest - Journal of Universal Studies, 2026)
This study aims to determine the role of leadership style and motivation in improving teacher performance at SMAN 7 Cirebon City. The approach used in this study was quantitative, with a research population of 117 teachers. The sampling technique used the saturated sample method, with all teachers as respondents. Data were collected through a Likert scale questionnaire of 1-5, then analyzed using the SPSS program. The data analysis process was carried out through several stages, namely testing the validity and reliability of research instruments, testing classical assumptions, and multiple linear regression analysis to see the role of leadership style and motivation in improving teacher performance. The results of the study show that 1). Leadership style has a negative and insignificant effect on teacher performance, 2). Motivation has a positive and significant influence on teacher performance.